A technique for the treatment of maxillary sinus membrane perforations occurred during endodontic surgery: a prospective comparative evaluation - Silvio Taschieri; Stefano Corbella; Massimo Del Fabbro (Giornale Italiano di Endodonzia, 2014)
Objectives: The aim of this study was to evaluate the use of PRGF in endodontic surgery to treat sinus membrane perforation. Materials and methods: A total of 20 patients (ten per group) were included. In the control group the lesion of the sinusal membrane was treated with collagen sponge. In the test group PRGF was used to close the communication with the sinus cavity. Results and conclusions: The use of PRGF resulted in better postoperative quality of life parameters if compared to the negative control group. Perceived pain was significantly lower in the test group than in the control one for the first six days after intervention.